Queer Voices in Hip Hop Cultures, Communities, and Contemporary Performance - Kehrer, Lauron J. (Tracking Pop, 2022)
Notions of hip hop authenticity, as expressed both within hip hop communities and in the larger American culture, rely on the construction of the rapper as a Black, masculine, heterosexual, cisgender man who enacts a narrative of struggle and success. In Queer Voices in Hip Hop, Lauron J. Kehrer turns our attention to openly queer and trans rappers and positions them within a longer Black queer musical lineage. Combining musical, textual, and visual analysis with reception history, this book reclaims queer involvement in hip hop by tracing the genre's beginnings within Black and Latinx queer music-making practices and spaces, demonstrating that queer and trans rappers draw on Ballroom and other cultural expressions particular to queer and trans communities of color in their work in order to articulate their subject positions. By centering the performances of openly queer and trans artists of color, Queer Voices in Hip Hop reclaims their work as essential to the development and persistence of hip hop in the United States as it tells the story of hip hop's queer roots.